PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERJUDIAN - Afriansyah, Ricky; Fahmi; Pardede, Rudi (LPPM STIH Awang Long, 2025)
The purpose of this research is to analyze the Law Enforcement Against Perpetrators of Gambling Crimes in the Jurisdiction of the Pekanbaru City Police, identify the obstacles in enforcing the law, and explore efforts to overcome these obstacles. The method used is sociological legal research. Based on the results, it is found that law enforcement against gambling offenders in the Pekanbaru City Police jurisdiction is not yet fully optimal, as gambling practices remain prevalent in the community—both in conventional forms such as lottery and card games, and in online forms such as slot games and chip-based games like Higgs Domino. Although the police routinely conduct raids and uncover cases, gambling persists due to various social and structural factors that sustain it. The obstacles in enforcing the law against gambling offenders in the jurisdiction of the Pekanbaru City Police are: First, the limited availability of digital forensic technology at the level of the criminal investigation unit, especially to uncover and act on online gambling involving foreign platforms and fictitious bank accounts. Second, the low level of community participation in providing valid reports or information to the police. It was observed that some community members still perceive gambling as normal, even as a form of entertainment or supplementary income. Third, the presence of legal loopholes in dealing with gambling through game-based applications such as Higgs Domino and similar platforms, as there are no clear regulations defining such games as gambling tools.